SISTEM PENDUKUNG KEPUTUSAN PENILAIAN KINERJA GURU BIMBINGAN BELAJAR MENGGUNAKAN METODE SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE (SMART) BERBASIS WEB - Nur Khakim , Muhammad; Dwi Indriyanti , Aries (Inovate, 2024)
Evaluation of teacher performance in a tutoring institution is an important and absolute thing to do to improve the quality of learning. This research was created with the aim of developing a decision support system for evaluating teacher performance using the Simple Multi Attribute Rating Technique (SMART) as the method. This research involved 15 respondents who were students from AHE tutoring institutions who were still active in the learning process. Using a predetermined rating scale, each participant gives an assessment of the teacher based on several criteria including: getting to know students, material assistance, class mastery, attendance, discipline, teaching behavior and teaching responsibilities. From the calculation of the system that has been carried out, the results of the study show that the teacher with the highest rating is Izza Kumalah Nur, S.Pd.I with a score of 0.7250, followed by Asti Nidya Agustin, S.Pd with a value of 0.7167, and in third place is won by Siti Nur Anisah with the value is 0.6500. The system that has been created is able to provide recommendations for the best teacher performance assessment based on respondents' assessments, which can help the leaders of tutoring institutions to identify teachers who excel in their learning process and can be used as evaluation material for teachers. Keywords: Teacher Performance Assessment, SMART Method, Decision Support System.